Five personality dimensions in patients with irritable bowel syndrome - Alireza Farnam (Dove Medical Press, 2008)
Alireza Farnam, Mohammad H Somi, Firouz Sarami, Sara FarhangLiver and Gastrointestinal Diseases Research Center, Tabriz University of Medical Sciences, Tabriz, IranAim: Irritable bowel syndrome (IBS) as a functional disorder of the gastrointestinal tract has been related to psychological factors. Aim of this study is to study the differences of personality factors between IBS patients compared to our general population.Methods: This study was performed in clinics of Tabriz Medical University during 2006–2007. IBS was diagnosed using the Rome II diagnostic criteria after exclusion of organic bowel pathology. The entry of each patient was confirmed following a psychiatric interview and after any comorbid psychiatry disorder was ruled out. Personality traits and score of each factor was evaluated using NEO five factor personality inventory compared to results of a previous study on general population of Iran.Results: One hundred and sixty six patients were studied. The mean age (±SD) of them was 33.6(±11.4) years (60.8% female). Our study population had their symptoms for a mean interval of 47.3 month. The bowel problems were provoked by distress in more than 80% of patients. Pain in female patients was reported to be more frequent but both gender described the association between stressors and their symptoms. NEO Five-Factor Inventory showed a significantly higher level of neuroticism and conscientiousness and lower level of openness and agreeableness in theses nonpsychiatric IBS patients. Women with IBS had significantly higher levels of openness, conscientiousness, and extraversion compared to men.Conclusion: Differences were observed between IBS patients and general population. Patients with IBS may benefit from psychological interventions.Keywords: irritable bowel syndrome, personality, five-factor model